Critical Management of Recurrent Seizure at 16-year-old Primigravida with Atypical Eclampsia - HS, Putu Ari Kamanjaya; Gunawan, Febri Jaya (Jurnal Komplikasi Anestesi, 2025)
Background: Atypical eclampsia can complicate the management and pose significant risks to both the mother and fetus. This case report emphasizes the critical management approach for recurrent seizures in a young primigravida. Case: A 16-year-old primigravida presented with sudden onset seizures during her third trimester of pregnancy. Initial assessments showed only a slight elevation of blood pressure and proteinuria, suggesting the presence of atypical eclampsia. Despite initially administering MgSO4, the patient still experienced a postpartum seizure. She was closely monitored and given a maintenance dose of midazolam and dexmedetomidine. After five days of treatment, the patient did not have any further convulsions and remained stable. Discussion: Teenage pregnancies increase the risk of maternal fatalities due to eclampsia. Atypical eclampsia is rare but can occur and requires a specific treatment approach. When therapy with magnesium sulfate is ineffective, midazolam and dexmedetomidine are used as alternative anti-epileptic drugs. Dexmedetomidine has a neuroprotective effect, preventing cerebral ischemia, and is effective in reducing the need for antihypertensive medication and hospitalization. Conclusion: The successful utilization of a combination of midazolam and dexmedetomidine highlights their potential as an effective therapeutic option for refractory seizures and adds to the existing treatment armamentarium for eclampsia.